Peranan Pelaku UMKM Perempuan bagi Perekonomian Keluarga di Kelurahan Tangga Takat Palembang (Studi Kasus UMKM Kuliner Tradisional) - Dian Candra Fatihah; Imelda Verawati; Ai Nunung (JKEN: Jurnal Kajian Ekonomi Nasional, 2026)
This article is titled “The Role of Female MSME Entrepreneurs in the Family Economy of Tangga Takat Subdistrict, Palembang.” This study aims to identify female MSME entrepreneurs in Tangga Takat Subdistrict, Palembang, as they navigate the surge of foreign food trends such as Korean and Japanese cuisine. The objective of the study is to determine the extent of the influence of these foreign food markets so that traditional food can remain the primary choice in an era of viral foreign food trends. The method used is qualitative analysis, and two (2) SME samples were selected from the main operators in Tangga Takat Village who are active in the traditional culinary sector. The research results indicate that female SME operators can compete through innovation to maintain the appeal of traditional food among people of all age groups, as traditional food possesses a distinctive flavor that resonates with the local community, particularly in Palembang. The challenges faced by female SME operators in the Tangga Takat neighborhood include the use of traditional promotional methods due to a lack of knowledge regarding technology and social media, as well as a lack of facilities, since most female SME operators conduct their production processes at home. Therefore, to overcome the challenges they face, women-owned SMEs must leverage technology and social media as promotional tools and actively participate in training seminars organized by the government to enhance their capabilities in the Tangga Takat neighborhood of Palembang. Keywords: SMEs, Women, Family Economy